2008
DOI: 10.1523/jneurosci.2642-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet and Fetal Programming: Increased Proliferation of Hypothalamic Peptide-Producing Neurons That Increase Risk for Overeating and Obesity

Abstract: Recent studies in adult and weanling rats show that dietary fat, in close association with circulating lipids, can stimulate expression of hypothalamic peptides involved in controlling food intake and body weight. In the present study, we examined the possibility that a fat-rich diet during pregnancy alters the development of these peptide systems in utero, producing neuronal changes in the offspring that persist postnatally in the absence of the diet and have long-term consequences. The offspring of dams on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
393
3
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(429 citation statements)
references
References 72 publications
22
393
3
11
Order By: Relevance
“…Consistent with the findings of Gorski et al (49), we found that exposure to a maternal cafeteria diet during both the fetal and suckling periods or suckling period alone, but not fetal period alone, was associated with a higher intake of fat, carbohydrate, and total energy when offspring were given free access to both a control and cafeteria diet at 2 mo of age (46). The inconsistencies between the study conducted by Chang et al (43) and those conducted by Gorski et al (49) and in our laboratory could potentially be explained by differences in the composition of the diet and the length of high-fat/cafeteria diet exposure before pregnancy; however, further investigation is clearly required. Nevertheless, the results of the latter 2 studies suggest that the suckling period, rather than the prenatal period, plays the more important role in the programming of food preferences.…”
Section: Critical Windows Of Development In the Programming Of Food Psupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with the findings of Gorski et al (49), we found that exposure to a maternal cafeteria diet during both the fetal and suckling periods or suckling period alone, but not fetal period alone, was associated with a higher intake of fat, carbohydrate, and total energy when offspring were given free access to both a control and cafeteria diet at 2 mo of age (46). The inconsistencies between the study conducted by Chang et al (43) and those conducted by Gorski et al (49) and in our laboratory could potentially be explained by differences in the composition of the diet and the length of high-fat/cafeteria diet exposure before pregnancy; however, further investigation is clearly required. Nevertheless, the results of the latter 2 studies suggest that the suckling period, rather than the prenatal period, plays the more important role in the programming of food preferences.…”
Section: Critical Windows Of Development In the Programming Of Food Psupporting
confidence: 90%
“…The findings of Chang et al (43) have not, however, been replicated in other cross-fostering studies. In one of these studies, Gorski et al (49) demonstrated that exposure to a high-fat diet during the suckling period alone was sufficient to increase the offspring's appetite for highenergy foods in adulthood.…”
Section: Critical Windows Of Development In the Programming Of Food Pmentioning
confidence: 80%
See 3 more Smart Citations